Columbia River Wildlife Mitigation Habitat Evaluation Procedures Report / Scotch Creek Wildlife Area, Berg Brothers, and Douglas County Pygmy Rabbit Projects. - Ashley, Paul R. (Washington (State). Department of Fish and Wildlife., 1997)
This Habitat Evaluation Procedure study was conducted to determine baseline habitat units (HUs) on the Scotch Creek, Mineral Hill, Pogue Mountain, Chesaw and Tunk Valley Habitat Areas (collectively known as the Scotch Creek Wildlife Area) in Okanogan County, Sagebrush Flat and the Dormaler property in Douglas County, and the Berg Brothers ranch located in Okanogan County within the Colville Reservation. A HEP team comprised of individuals from the Washington Department of Fish and Wildlife, the Confederated Tribes of the Colville Reservation, and the Natural Resources Conservation Service (Appendix A) conducted baseline habitat surveys using the following HEP evaluation species: mule deer (Odocoileus hemionus), sharp-tailed grouse (Tympanuchus phasianellus), pygmy rabbit (Brachylagus idahoensis), white-tailed deer (Odocoileus virginiana), mink (Mustela vison), Canada goose (Branta canadensis), downy woodpecker (Picoides pubescens), Lewis woodpecker (Melanerpes lewis), and Yellow warbler (Dendroica petechia). Results of the HEP analysis are listed below. General ratings (poor, marginal, fair, etc.,) are described in Appendix B. Mule deer habitat was marginal lacking diversity and quantify of suitable browse species. Sharp-tailed grouse habitat was marginal lacking residual nesting cover and suitable winter habitat Pygmy rabbit habitat was in fair condition except for the Dormaier property which was rated marginal due to excessive shrub canopy closure at some sites. This report is an analysis of baseline habitat conditions on mitigation project lands and provides estimated habitat units for mitigation crediting purposes. In addition, information from this document could be used by wildlife habitat managers to develop management strategies for specific project sites.